2016
DOI: 10.1080/08977194.2016.1210142
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CTGF is independently related to an increased risk of cardiovascular events and mortality in patients with atherosclerotic disease: the SMART study

Abstract: In patients with manifest vascular disease, elevated plasma CTGF confers an increased risk of new cardiovascular events and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
0
13
1
1
Order By: Relevance
“…SBP was shown to be significantly associated with the continuous part under the Weibull distribution, but not with lognormal or gamma distributions. This result is not in line with findings from other clinical studies that showed a significant association between hypertension and CTGF [ 7 , 9 ]. The discrepancy in the inferences between the mTP model and the TP model with uncorrelated random effect could be attributed to the increased lack of efficiency, and bias in the parameter estimates due to ignoring the correlation between the random effects in the two components and fitting the zero and continuous parts separately [ 21 , 28 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…SBP was shown to be significantly associated with the continuous part under the Weibull distribution, but not with lognormal or gamma distributions. This result is not in line with findings from other clinical studies that showed a significant association between hypertension and CTGF [ 7 , 9 ]. The discrepancy in the inferences between the mTP model and the TP model with uncorrelated random effect could be attributed to the increased lack of efficiency, and bias in the parameter estimates due to ignoring the correlation between the random effects in the two components and fitting the zero and continuous parts separately [ 21 , 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Plasma CTGF levels were independently associated with hypertension, increased albumin excretion rate, increased carotid intima-media thickness, hemoglobin A1c (HbA1c) and circulating levels of lipoproteins [ 7 ]. Plasma CTGF was also linked to increased risk of cardiovascular events and mortality in patients with atherosclerotic disease and was associated with plaque stabilization following stroke [ 8 , 9 ]. Moreover, plasma CTGF levels were shown to predict myocardial infraction in type 2 diabetic subjects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inhibition of CTGF in the cardiovascular system was shown to reverse tissue remodeling and the process of fibrosis (37). Moreover, plasma CTGF was linked to an increased risk of cardiovascular events and mortality in patients with atherosclerotic disease and was associated with plaque stabilization after stroke (12,15). Although the exact mechanisms through which CTGF mediates its inflammatory and fibrotic effects on the vasculature are not fully defined, engagement of all six members of integrin receptors and binding to heparin sulfate proteoglycans such as syndecan-4, LDL-related receptor protein, and the cation-independent mannose-6-phosphate receptor have been implicated as key factors through which CTGF transduces its cellular effects (38).…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of CTGF/CCN2 expression has been linked to various fibroproliferative disorders including diabetes complications and atherosclerosis (8,9). An emerging role of CTGF/CCN2 is that of a prosclerotic factor implicated in the development of cardiac disease (10)(11)(12)(13)(14)(15). CTGF/CCN2 expression is upregulated in cardiac tissue after myocardial infarction (MI) and has been shown to modulate cardiac function and tissue remodeling (16,17).…”
mentioning
confidence: 99%
“…There are, to our knowledge, no other reports from large STEMI cohorts on CCN2 and long-term prognosis. A recent report, however, demonstrated that high baseline plasma levels of CCN2 were associated with increased risk of mortality and cardiovascular events, in patients with manifest, but stable, vascular disease 20 , in contrast to the hypothesis that high levels of CCN2 should be cardioprotective. It must be emphasised that this was a completely different patient population compared to our acute MI populations.…”
Section: Discussionmentioning
confidence: 88%